If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(5x + -6) + -1ln(3x + -1) = 0 Reorder the terms: ln(-6 + 5x) + -1ln(3x + -1) = 0 (-6 * ln + 5x * ln) + -1ln(3x + -1) = 0 (-6ln + 5lnx) + -1ln(3x + -1) = 0 Reorder the terms: -6ln + 5lnx + -1ln(-1 + 3x) = 0 -6ln + 5lnx + (-1 * -1ln + 3x * -1ln) = 0 -6ln + 5lnx + (1ln + -3lnx) = 0 Reorder the terms: -6ln + 1ln + 5lnx + -3lnx = 0 Combine like terms: -6ln + 1ln = -5ln -5ln + 5lnx + -3lnx = 0 Combine like terms: 5lnx + -3lnx = 2lnx -5ln + 2lnx = 0 Solving -5ln + 2lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(-5 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-5 + 2x)' equal to zero and attempt to solve: Simplifying -5 + 2x = 0 Solving -5 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 0 + 5 2x = 0 + 5 Combine like terms: 0 + 5 = 5 2x = 5 Add '-2x' to each side of the equation. 2x + -2x = 5 + -2x Combine like terms: 2x + -2x = 0 0 = 5 + -2x Simplifying 0 = 5 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| H=-16t^2+80t+1 | | 2(4+3)+2=-4(x+1) | | -7x+6=-8 | | 9h^2+4=4 | | 2x=4x+8 | | -3(4s-2)-6=-3(9s+3)-5 | | 4x+-22=-2 | | -4.4x-3=-3.9x+2 | | .5-2= | | 8(w-2)=16 | | 14x+5= | | 72=-9x | | x^2+12x-576=0 | | -4x+12=-32 | | k+89.2=-.2 | | 45(5x-5)=25(x-1) | | 6a^2-13a-28=0 | | 3x^2-6x+7=0 | | x+(x-30)=150 | | -54+24=-2x+8x | | x^2-14x+y^2-150y=-49 | | -5z=20 | | -2x+3+3x=-7+23 | | a/3=9-4 | | x^2+2x-44=0 | | 9(z+4)-41=0 | | ln(x)=3.57 | | 6w^2-19w-20=0 | | 14+16/5= | | 14+16= | | In(x)=3.57 | | 7zx+4=5x+5 |